2010
DOI: 10.1108/13598541011080437
|View full text |Cite
|
Sign up to set email alerts
|

Information sharing and collaboration practices in reverse logistics

Abstract: 2010),"Collaborative supply chain practices and performance: exploring the key role of information quality", SupplyIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
124
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(134 citation statements)
references
References 30 publications
5
124
0
2
Order By: Relevance
“…This study also measured collaboration in terms of information sharing and joint planning and decision making. Future studies should also consider the incentive alignment (Simatupang and Sridharan, 2005) and risk-and reward-sharing dimensions and joint performance evaluation dimensions of collaboration (Olorunniwo and Li, 2010).…”
Section: Limitations and Areas For Further Studymentioning
confidence: 99%
“…This study also measured collaboration in terms of information sharing and joint planning and decision making. Future studies should also consider the incentive alignment (Simatupang and Sridharan, 2005) and risk-and reward-sharing dimensions and joint performance evaluation dimensions of collaboration (Olorunniwo and Li, 2010).…”
Section: Limitations and Areas For Further Studymentioning
confidence: 99%
“…They further stated that most studies on reverse logistics have been carried out in developed countries. Reverse logistics practices that have been identified in previous studies include product returns and remanufacturing (Olorunniwo and Li, 2010), recovery, recycling and reuse (Field and Sroufe, 2007) and redistribution (Das, 2012). These practices apply to final products, their components (Das, 2012), and packaging material (Field and Sroufe, 2007).…”
Section: Reverse Logistics Practicesmentioning
confidence: 99%
“…For instance, Harris et al (2011) explored the relationship between total logistics cost and environment impact in terms of CO 2 emissions for strategic modelling in an automotive logistics network, and found that the optimum design of a distribution network is highly sensitive to the level of vehicle utilisation and the optimum design based on costs does not simultaneously generate an optimum solution for CO 2 emissions. Wu and Dunn (1995) pointed out that there is a need to integrate reverse logistics into the total logistics framework in order to design an environmentally responsible logistics system and Olorunniwo and Li (2010) identify that ICT has a major role to play in that integration.…”
mentioning
confidence: 99%